The relationship between perceptions of non-formal education and perceptions of 21st-century skills in a religious-collectivist community - Barth, Anat; Cahaner, Lee; Ruchwarger, Shneor (Frontiers in Education, 2026)
IntroductionThis study examines the relationship between ultra-Orthodox teachers’ perceptions of non-formal education and their perceptions of 21st-century skills. These skills comprise a set of competencies essential for successful integration into today’s workforce and civic life. Teachers’ perceptions of these skills and their importance are critical for their successful implementation in the classroom. Several factors contribute to teachers’ positive perceptions of 21st-century skills, one of which is a positive view of non-formal education, which is a flexible, investigative, and creative educational method. This research explores this relationship by focusing on teachers from the ultra-Orthodox collectivist culture, a community that tends to show conflicting attitudes toward 21st-century skills and non-formal education.MethodsA group of 238 ultra-Orthodox teachers completed a questionnaire regarding perceptions of non-formal education, 21st-century skills and demographic data.ResultsThe findings indicate that positive perceptions of non-formal education are associated with all dimensions of 21st-century skills, with the strongest related to communication skills, which is aligned with cultural norms, while creativity showed the weakest association, which also reflects a broad cultural rejection of this skill.DiscussionThe study reinforces the positive connection between educational approaches and perceptions of 21st-century skills, including within a religious collectivist community.